Maggot Cultivation: Qur'anic Economic Empowerment with Environmental Insight - Febriani, Ina (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Lingungan Hidup, 2024)
Environmental problems and unemployment are currently serious discussion. This is proven by the piling up of garbage as well as the high unemployment rate, especially in Banten Province. These two problems able to overcome by utilizing decomposer organism that have been created by Allah SWT, as we know is black soldier fly (BSF) or maggot. Unfortunately, the use of maggot to minimize waste and unemployment has not run optimally. The research method is using descriptive qualitative method. The information obtained through observation. Interviews, literature studies and documenting related to maggot cultivation. This research was conducted to overcome the problems of accumulating waste, it can also create jobs for the community through maggot cultivation. Based on the result of this research, cultivating maggot can open jobs and care on the environment. With the discovery that maggot cultivation can create jobs, it is hoped that one of the SDGs goals; decent work and economic growth that can be fulfilled. Besides that, it can minimize piles of waste, especially organic waste.